Efektivitas Edukasi Bahasa Arab dalam Meningkatkan Literasi Bahasa Arab Siswa Madrasah Ibtidaiyyah - Rifa’i, Much Rachmat; Nafisah, Lulu; Zakiyah, Nur; Khobir, Abdul; Mahmudah, Umi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2021)
This study aims to analyze the effectiveness of Arabic language education activities in improving the ability of children at Madrasah Ibtidaiyah level in reading Arabic books through. In this study, the researcher used a mixed method, which combines quantitative and qualitative methods. Quantitative data were obtained using a test instrument. Meanwhile, qualitative data were obtained by direct interviews with children. The research sample was 22 respondents who were MI level children in Blarakan village, Kebulen district, Pekalongan. Quantitative data analysis used the paired sample t-test method with the help of SPSS software. The results of the study indicate that Arabic language education activities have a significant effect on increasing Arabic language skills. In other words, Arabic education activities are more effective in helping children to improve their reading skills in Arabic. In addition, the results of the analysis also indicate that before the Arabic language education activities were carried out, the children's reading ability was classified as moderate.